High rates of unprotected anal sex and use of generic direct‐acting antivirals in a cohort of MSM with acute HCV infection. Issue 6 (18th February 2019) - Girometti, Nicolò; Devitt, Emma; Phillips, Joe; Nelson, Mark; Whitlock, Gary
Summary: The role of condomless anal intercourse (CAI) as a driver for the epidemic of hepatitis C in MSM is still debated. Timely access to direct‐acting antivirals (DAA) could represent an essential strategy to tackle this. Case notes of MSM diagnosed with acute hepatitis C (AHC) between July 2016 and June 2017 in a sexual health clinic in London were included. Behavioural data on sexual practices and STI monitoring in the 6 months prior to AHC diagnosis were collected. DAA routes of access and timing from AHC diagnosis to start of treatment were analysed. A total of 60 individuals were enrolled (median age 39 years, IQR = 33‐46, 62% HIV co‐infected, 72% genotype 1a). CAI was reported by 97%, drug use prior to or during sex by 73%; 46% was diagnosed with a rectal STI and 29% with syphilis. About 37% did not report any HCV risk factors other than condomless anal sex. About 36% had a new rectal STI in the 6 months following AHC. About 82% accessed DAA treatment and median time from AHC to DAA start was 278 days for those following the NHS standard of care route, 132 days for those accessing DAA via participation in trials and 114 for those who had self‐sourced DAA online ( P <  0.0011 ) . SVR12 was achieved in 100% of the patients who received DAA treatment.In conclusion, CAI is a significant risk factor for HCV acquisition in MSM, irrespective of their HIV status. Rapid and wider access to treatment with DAA could represent a powerful strategy to reduce onward transmission and risk of reinfection in MSM.